The Quality of the Online Mail Information System and Its Influence on Service Satisfaction for Students of the Faculty of Teacher Training and Education Sriwijaya University - Agung Dwi Rizky; Katriza Imania; Muhammad Nur Budiyanto (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study seeks to examine the impact of system quality, information quality, and service quality on user satisfaction with the online mail system among students at the Faculty of Teacher Training and Education (FKIP) at Sriwijaya University. Data were collected via a quantitative survey approach utilizing questionnaires and analyzed through multiple linear regression. The results indicate that system quality, information quality, and service quality positively and significantly influence user satisfaction. This suggests that enhancing system and information quality directly elevates student satisfaction. Thispoints out the importancethe necessity of creating a responsive, informative, and user-friendly online mail system. The administration of FKIP Universitas Sriwijaya ought to leverage these findings to foster ongoing enhancement, concentrating on the augmentation of technological infrastructure, data precision, and user service responsiveness to elevate administrative efficiency and the faculty's service reputation. This study theoretically enhances the DeLone and McLean model regarding digital academic services and offers practical recommendations for managing technology-based services in higher education settings.